Successful employees’ adaptive performance at Sharp Manufacturing Corporation (M) Sdn. Bhd. in Batu Pahat / Nurfazliana Faizul - Faizul, Nurfazliana (Faculty of Business and Management, 2019)
Modern work is frequently characterized by jobs where adaptive performance (AP) is crucial for employees to succeed in light of new or altered task demands. This recognition has fueled growing interest in AP as a dimension of workplace performance. Hence, successful employees’ adaptive performance has become one of the most prized way to achieve organizational performance. The purpose of this research is to investigate the factors that leads to successful employees’ adaptive performance in organizations. This research is a quantitative research which had used the self-administered questionnaire as the instrument for the collection of data. The data was collected and viable at a percentage of 74% out of the possible 248 respondents which was derived from the population of 700 elements. Sample selection was based on simple random sampling method. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 20 Software. Using SPSS, numerous tests were converged such as reliability analysis, frequency distribution, descriptive analysis, Pearson’s correlation analysis and multiple regression. The results indicated that transformational leadership, readiness for change and organizational learning had contributed significantly to the adaptive performance.